Alpheus naranjo, a new brightly coloured snapping shrimp from the Caribbean coast of Panama (Malacostraca, Decapoda, Alpheidae) - Anker, Arthur (Zootaxa, 2018)
A new snapping shrimp is described based on several specimens collected on a shallow coral reef off Isla Popa in Bocas del Toro, on the Caribbean coast of Panama. All specimens of Alpheus naranjo sp. nov. were extracted from dead colonies of the thin-leaf lettuce coral, Agaricia tenuifolia Dana, at a depth of about 2 m. Based on its morphological characteristics, the new species belongs to a small species complex that also includes A. blachei Crosnier & Forest, 1965 from the tropical eastern Atlantic, and A. felgenhaueri Kim & Abele, 1988 and A. confusus Carvacho, 1989, both from the tropical eastern Pacific. Alpheus naranjo sp. nov. can be separated from all of them by the relatively longer fingers of the minor chela, which are devoid of balaeniceps setae, as well as some other morphological details. In the western Atlantic, A. naranjo sp. nov. is the only large uniformly orange-red snapping shrimp, hence its proposed new name. The colour patterns of A. blachei and A. confusus are illustrated for the first time.